Electricity Market Nash-cournot Equilibrium Analysis with High Proportion of Gas-fired Generators. (May 2017) - Chen, Gang; Lu, En; Zeng, Kaiwen; Dong, Chao; Hu, Shizhao; Guo, Hongye; Chen, Qixin
Abstract: With the increasing penetration of renewable energy in the power system and stricter restrictions on the air pollutants, more gas-fired generators have been accessed into the power system. To analyze the impacts of high proportion of gas-fired units on the power system, a liberalized electricity market Nash-Cournot equilibrium model has been proposed in this paper. Then a numerical example is given to present the influence of high proportion of gas-fired units on the energy price, demand and the accommodation of renewable energy in the market equilibrium. Comparisons between high and low proportion of gas-fired units in the power systems are also presented.